Conspicuous Consumption in Emerging Markets: The Case of Starbucks in Colombia as a Global and Sustainable Brand - Areiza-Padilla, Jose Andres; Manzi Puertas, Mario Andres (Frontiers in Psychology, 2021)
Conspicuous consumption symbolizes ostentatious and material consumption, through the purchase of products and services with a higher economic value, and that allow their consumers to excel socially. However, conspicuous consumption often does not represent social and environmental values, because their products are often not characterized by being made through sustainable processes. United Nations, through its sustainable development agenda, invited companies to be aware of the social and environmental problems of the world and to be able to generate strategies that can be sustainable over time and allow the growth of both the company and society in general. This study analyzes the case of Starbucks, as a global brand, and that performs sustainable processes, in addition to generating a conspicuous consumption that emerging markets. In this way, we explain how this brand generates a social status in emerging markets, which allow their consumers to excel socially. On the other hand, we explain how Starbucks contributes positively to sustainability in these types of markets, generating greater wellbeing for both the environment and society in general. In this way, this brand manages to transmit messages with symbolic values of social status, as well as social and environmental awareness. This research allows us to see how Starbucks is able to generate conspicuous consumption in Colombia, which is the third largest exporter of coffee in the world, but is also capable of generating sustainable processes that help Colombian coffee growers and the environment. This research used a quantitative methodology based on a structured questionnaire made to conspicuous consumers of the Starbucks brand in Colombia, whose data were processed through the statistical program PLS 3.2.7. This research details what are the sustainable processes carried out by this brand in this developing country, and why its consumption in this emerging market is considered conspicuous. For this research, family allocentrism, ethnocentrism, and patriotism are considered antecedents of conspicuous consumption, and brand image and brand loyalty are considered its results.